Inheritance and influence of histocompatibility (HL-A) antigens in adult coeliac disease. Issue 8 (August 1973) - Stokes, P. L.; Asquith, P.; Holmes, G. K. T.; Mackintosh, Pauline; Cooke, W. T.
Abstract : In a study of histocompatibility antigens in adult coeliac disease the HL-A phenotypes have been determined in 117 patients and 149 of their first-degree relatives, of whom 94 had had a jejunal biopsy performed. There was an increased frequency of the HL-A 8 antigen in the patients and their relatives. Family studies showed no irregularity in the inheritance of both this antigen and the HL-A 1 and 8 haplotype.